Infrared heat radiation nanometer reflecting plate for road surface hot in-place recycling heating unit
By using nano-coated reflector plates made of nano-titanium dioxide and nano-alumina in the on-site thermal regeneration heating unit on the road surface, the problems of insufficient high temperature resistance and corrosion resistance of existing reflector plates are solved, and efficient infrared thermal radiation reflection and heating efficiency are achieved.
Patent Information
- Application Number
- CN202510074076.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
When used in on-site heat regeneration heating units on the road, the existing infrared heat radiation reflector plates have insufficient high temperature resistance and corrosion resistance, resulting in a decrease in infrared reflection efficiency and affecting heating efficiency and energy consumption control.
Nanocoatings with nanotitanium dioxide and nanoalumina as the main components are combined with silicone high-temperature binder and high molecular weight polyacrylate dispersant to form ultra-smooth, high temperature and corrosion-resistant infrared heat radiation nanoreflection plates.
It significantly improves infrared thermal radiation reflectivity, improves the efficiency and energy utilization of road surface heating, reduces energy consumption, and maintains the integrity and smoothness of the coating in high temperature environments.
Smart Images

Figure BDA0005246519510000061 
Figure BDA0005246519510000073 
Figure BDA0005246519510000081
Abstract
Description
Technical Field
[0001] The invention relates to an infrared heat radiation nano reflector, in particular to an infrared heat radiation nano reflector for a road surface in-situ heat regeneration heating unit, and belongs to the technical field of road maintenance machinery. Background Art
[0002] As the core machinery of modern road maintenance, the in-situ heat regeneration heating unit of the road surface relies on the thermal effect of infrared thermal radiation to achieve the softening and regeneration of old road surface materials.
[0003] However, the existing conventional reflectors have significant disadvantages. When the traditional metal reflectors (stainless steel, aluminum, etc.) are subjected to the high operating temperature of the unit for a long time, the surface will quickly oxidize and the structure will deform, resulting in a sharp decrease in infrared reflection efficiency; conventional coating reflectors ( Diffuse reflection standard plate, etc.) is mostly used to reflect solar radiation and is widely used in building insulation, electronic display screens, optical instruments, and car windows. For example, an infrared radiation roof based on phase change materials, patent number: CN222101300U; an intelligent integrated optical component based on digital power control, patent number: CN105387393A, etc. If used in a road in-situ heat regeneration heating unit, the coating performance will be reduced when the unit is subjected to high operating temperature for a long time, the adhesion will be poor, it will be easy to peel off, and the reflection efficiency of infrared thermal radiation (1.4-15μm) will be reduced.
[0004] Therefore, in view of the high requirements of the in-situ heat regeneration heating unit for the infrared heat radiation reflective plate's infrared reflectivity, surface roughness, high temperature resistance and corrosion resistance, it is urgent to develop an infrared heat radiation nano reflective plate for the in-situ heat regeneration heating unit of the pavement, which has the characteristics of high infrared reflectivity, ultra-smoothness, good high temperature resistance and corrosion resistance, so as to meet the needs of efficient, energy-saving and long-lasting in-situ heat regeneration operations of the pavement. Summary of the invention
[0005] The technical problem solved by the present invention is: to overcome the shortcomings of the prior art and propose an infrared thermal radiation nano-reflector for a pavement in-situ thermal regeneration heating unit. The infrared thermal radiation nano-reflector has the characteristics of high infrared reflectivity, ultra-smoothness, good high temperature resistance and corrosion resistance. It can be used in a pavement in-situ thermal regeneration heating unit to significantly improve the infrared thermal radiation reflectivity of the unit, thereby improving the heating efficiency of the unit when heating the pavement and reducing energy consumption. It has broad application prospects in efficient, energy-saving and long-lasting pavement in-situ thermal regeneration operations.
[0006] The technical solution of the present invention is:
[0007] The invention discloses an infrared heat radiation nano reflector for a road surface in-situ heat regeneration heating unit, comprising a substrate, wherein the surface of the substrate is sprayed with a nano coating; the components of the nano coating include the following raw materials in parts by weight: 34 parts of nano titanium dioxide, 20-24 parts of nano aluminum oxide, 14-18 parts of an organic silicon high temperature binder, 5-7 parts of a dispersant, and 17-27 parts of anhydrous ethanol solvent; the nano titanium dioxide has an average particle size of 30-40 nm, and exhibits excellent scattering and reflection capabilities in the 1.4-15 μm infrared band by virtue of its unique crystal structure and electronic transition characteristics, while also having photocatalytic self-cleaning potential to keep the surface of the reflector clean; the nano aluminum oxide has an average particle size of 40-50 nm; the overall structure of the coating is reinforced with high melting point and high hardness characteristics, and the high temperature resistance is synergistically improved; the dispersant is a high molecular weight polyacrylate ammonium salt dispersant with a molecular weight range of 100,000-400,000 g / mol, and through the dual mechanisms of electrostatic repulsion and steric hindrance, the dispersion of the nanoparticles exceeds 95%, thereby ensuring the microscopic uniformity of the coating.
[0008] Furthermore, the substrate is aluminum alloy 6061 or titanium alloy TC4.
[0009] The organosilicon high temperature adhesive is MS polymer adhesive, specific model: XT55, in a high temperature environment above 320°C, has a bonding strength retention rate of no less than 80%, and can strongly anchor the coating and the substrate.
[0010] When preparing the nano coating, under a constant temperature and humidity environment, each raw material is accurately weighed, and nano titanium dioxide, nano aluminum oxide, silicone high-temperature binder, and dispersant are added to anhydrous ethanol in proportion to obtain a solution; then the solution is placed in a high-speed stirrer and stirred continuously at a speed of 1200-1400 rpm for 70-90 minutes until the solution has uniform color, good fluidity, and no visible agglomerates, thereby obtaining a nano coating.
[0011] The spraying preparation of the thermal radiation nano reflector includes two parts: substrate pretreatment and nano coating spraying and curing. The substrate pretreatment includes the following steps:
[0012] Grinding: Use an automatic sandblasting machine for surface treatment or use 300-grit sandpaper for manual grinding until the surface roughness Ra is 0.9-1.1μm;
[0013] Degreasing: Soak in acetone for 10-15 minutes for deep degreasing to completely remove oil and impurities;
[0014] Rinse and dry: Rinse with deionized water at high pressure for 3-5 minutes to ensure no impurities remain, then dry.
[0015] When spraying and curing the nano coating, a spray gun is used to evenly spray the nano coating, the air pressure of the spray gun is stabilized at 0.45-0.55MPa, and the spray thickness is precisely controlled at 60-80μm. After the spraying operation is completed, it is cured for 70-90 minutes in a constant temperature and humidity environment. Furthermore, the spraying and curing can be repeated 2-3 times, and the final coating thickness is 150-180μm.
[0016] The above-mentioned constant temperature and humidity environment is a temperature of 25±2°C and a humidity of 50±5%.
[0017] Compared with the prior art, this application has at least the following beneficial technical effects:
[0018] (1) The present invention designs and develops an infrared heat radiation nano-reflector for use in an on-site heat regeneration heating unit for a road surface, which has excellent ultra-smooth surface properties (Ra ≤ 0.1 μm), high temperature resistance (zero coating shedding after 100 times of 300°C high temperature cycle impact) and corrosion resistance.
[0019] (2) The present invention has designed and developed an infrared heat radiation nano reflector for a road surface in-situ heat regeneration heating unit, wherein the thickness of the nano coating reaches 150-180 μm, and the reflection efficiency of the infrared heat radiation band (1.4-15 μm) under high temperature environment reaches more than 85%, and the infrared heat radiation band (4-5 μm) that plays a major role in the in-situ heat regeneration unit shows an extremely high reflectivity (87%-89%). The present invention can significantly improve the thermal utilization efficiency of the in-situ heat regeneration heating unit, reduce energy consumption, and enhance the overall uniformity of road surface heating. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the embodiments.
[0021] Example 1
[0022] An infrared heat radiation nano reflector for a road surface in-situ heat regeneration heating unit, which is obtained by spraying a nano coating on the surface of a substrate; the specific method is as follows;
[0023] (1) According to the formula, 34 parts of nano titanium dioxide, 20 parts of nano aluminum oxide, 15 parts of organic silicon high temperature adhesive, 5 parts of polyacrylate ammonium salt dispersant (molecular weight 200000g / mol), and 26 parts of anhydrous ethanol are carefully taken. The organic silicon high temperature adhesive is MS polymer (modified silane) adhesive, specific model: XT55, manufacturer and seller: Wacker Chemical (China) Co., Ltd., the adhesive has a bonding strength retention rate of no less than 80% in a high temperature environment above 320°C, and strongly anchors the coating and the substrate;
[0024] (2) The high-speed agitator was operated at a steady speed of 1300 rpm for 85 minutes.
[0025] (3) A 6061 aluminum alloy plate with a thickness of 6 mm was selected as the substrate, which was sanded to an Ra of 1 μm, degreased with acetone, and rinsed and dried with deionized water.
[0026] (4) Spray with a spray gun at 0.5 MPa to a thickness of 160 μm and cure for 75 minutes in a constant temperature and humidity experimental environment (temperature 25±2°C, humidity 50±5%).
[0027] (5) The finished reflective plate was tested by a professional spectrometer. After 100 cycles of 300°C high-temperature impact, the reflectivity in the 1.4-15μm band soared to 86%, and the reflectivity in the 4-5μm band soared to 89%. The coating did not fall off. Thermal imaging showed that the heat uniformity of the unit's heating area was improved by 15%, and energy consumption was reduced by 12%.
[0028] Example 2
[0029] (1) Fine-tune the formula to 34 parts of nano titanium dioxide, 22 parts of nano aluminum oxide, 16 parts of organic silicon high temperature binder, 6 parts of polyacrylate ammonium salt dispersant (molecular weight 300,000 g / mol), and 22 parts of anhydrous ethanol.
[0030] (2) Stir at 1400 rpm for 90 minutes.
[0031] (3) Substrate treatment is the same as in Example 1.
[0032] (4) Spray with a spray gun at 0.48 MPa to a thickness of 170 μm and cure for 85 minutes in a constant temperature and humidity experimental environment (temperature 25±2°C, humidity 50±5%).
[0033] (5) After 100 cycles at 300°C, the reflectivity of the reflector reached 88% in the 1.4-15μm band and soared to 89% in the 4-5μm band. The coating was intact and the surface was smooth. Thermal imaging showed that the thermal field uniformity of the unit was optimized by 20% and energy consumption was reduced by 16%.
[0034] Example 3
[0035] (1) Fine-tune the formula to 34 parts of nano titanium dioxide, 24 parts of nano aluminum oxide, 17 parts of organic silicon high temperature binder, 5 parts of polyacrylate ammonium salt dispersant (molecular weight 400000 g / mol), and 20 parts of anhydrous ethanol.
[0036] (2) Stir at 1400 rpm for 80 minutes.
[0037] (3) Titanium alloy TC4 is selected as the substrate, and the substrate treatment is the same as in Example 1.
[0038] (4) Spray with a spray gun at 0.48 MPa to a thickness of 180 μm and cure for 80 minutes in a constant temperature and humidity experimental environment (temperature 25±2°C, humidity 50±5%).
[0039] (5) After 100 cycles at 300°C, the reflectivity of the reflector reached 85% in the 1.4-15μm band and soared to 88% in the 4-5μm band. The coating was intact and the surface was smooth. Thermal imaging showed that the thermal field uniformity of the unit was optimized by 18% and energy consumption was reduced by 15%.
[0040] Comparative Example 1
[0041] (1) Under the normal working environment of the road surface heat regeneration heating unit, select 6mm thick stainless steel.
[0042] (2) According to the detection of professional spectrometer, the reflectivity in the 1.4-15μm band is 78%, and the reflectivity in the 4-5μm band is 75%. After 100 times of 300℃ high temperature cycle impact, the surface of the stainless steel plate is oxidized, and the reflectivity in the 1.4-15μm band is reduced to 58%, and the reflectivity in the 4-5μm band is reduced to 51%. The surface roughness Ra>1.6μm, which affects the reflection uniformity of infrared thermal radiation.
[0043] Comparative Example 2
[0044] (1) Select a 6mm thick conventional coated reflector ( diffuse reflectance standard plate).
[0045] (2) According to the test by a professional spectrometer, the reflectivity in the 1.4-15μm band is 90%, and the reflectivity in the 4-5μm band is 89%. However, after 100 cycles of high-temperature impact at 300°C, the coating is severely oxidized and peeled off, and the reflectivity in the 1.4-15μm band is reduced to 67%, and the reflectivity in the 4-5μm band is reduced to 65%.
[0046] The infrared thermal radiation nano-reflection plates prepared in the above embodiments 1-3 have infrared reflectivity higher than 85%, and after 100 times of 300°C high temperature cycle impact, the coating is intact and the surface is smooth, which optimizes the heating uniformity of the unit by about 20% and reduces energy consumption by about 15%.
[0047] Comparative Example 1 Compared with Examples 1-3, the conventional metal reflector (stainless steel) was used. After 100 cycles of 300°C high temperature impact, the surface was rapidly oxidized and the structure was deformed, resulting in a sharp decrease in infrared reflection efficiency. Comparative Example 2 Compared with Examples 1-3, the conventional coating reflector ( Diffuse reflection standard plate), after 100 times of 300℃ high temperature cycle impact, the coating performance is reduced, the adhesion becomes poor, it is easy to peel off, and the reflectivity of infrared thermal radiation (1.4-15μm) is reduced.
[0048] Table 1 below is a performance test comparison table of the present invention and other metal plates and reflective plates:
[0049] The technical effects of the above embodiments and comparative examples are shown in the following table:
[0050] Table 1: Performance test comparison table
[0051]
[0052] Note: Unless otherwise specified, the technical indicators are measured after 100 cycles of 300℃ high temperature impact.
[0053] Conclusion: From Table 1, it can be seen that after 100 cycles of 300℃ high temperature impact, the infrared heat radiation nano reflector has a reflectivity of more than 85% for infrared radiation (1.4-15μm), and a reflectivity of more than 87% for the main infrared heat radiation band (4-5μm) that plays a heating role in the local heat regeneration unit. Compared with traditional metal reflectors (stainless steel, aluminum plates, etc.) and conventional coating reflectors ( Compared with diffuse reflection standard plates, the infrared (4-5μm) reflection efficiency is increased by 65% and 37% respectively. It can still efficiently reflect infrared thermal radiation in high temperature environments, increasing the thermal utilization efficiency of the unit by 12%-16%. In addition, after 100 cycles of 300℃ high temperature impact, the infrared thermal radiation nano reflector is 100 times better than traditional metal reflectors (stainless steel, aluminum plates, etc.) and conventional coating reflectors ( Compared with diffuse reflection standard plates, etc., the coating is firm and the structure is stable, and it can still maintain ultra-smooth (Ra≤0.1μm) surface characteristics, optimizing the heating uniformity of the unit by about 20%.
[0054] Example 4
[0055] On the basis of Example 1, only the amount of nano-alumina was changed, and the performance test was performed again, as shown in Table 2 below:
[0056] Table 2
[0057]
[0058] Note: The cross-cut test adopts the international standard ISO2409 "Coatings and varnishes - Cross-cut test" for grade assessment.
[0059] Conclusion: The above table shows that when the weight dosage of nano-alumina is less than 20 parts, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply, below 85%. The surface roughness Ra>0.1μm after 100 times of 300℃ high temperature cycle impact. The adhesion level is level 1, the edge of the coating is slightly peeled off, and the affected area is ≤5%;
[0060] At 20-24, the coating has a high reflectivity of infrared radiation (1.4-15μm band), higher than 85%, and when the weight dosage of nano-alumina is 22 parts, the reflectivity is 89%, the highest. The surface roughness Ra after 100 times of 300℃ high temperature cycle impact is <0.1μm, indicating super smoothness. The adhesion grade is 0, the coating edge is intact, without any peeling;
[0061] When the temperature is higher than 24, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The surface roughness Ra>0.1μm after 100 times of 300℃ high temperature cycle impact. The adhesion level is level 1, the edge of the coating is slightly peeled off, and the affected area is ≤5%;
[0062] Taking into account the infrared reflection efficiency (1.4-15 μm band and 4-5 μm band), surface roughness and adhesion of the coating, the weight amount of nano-aluminum oxide is preferably 20-24 parts, and the optimal value is 22 parts.
[0063] Example 5
[0064] On the basis of Example 1, only the amount of the organic silicon high temperature adhesive was changed, and the performance test was performed again, as shown in the following Table 3:
[0065] Table 3
[0066]
[0067] Note: The cross-cut test adopts the international standard ISO2409 "Coatings and varnishes - Cross-cut test" for grade assessment.
[0068] Conclusion: The above table shows that when the weight dosage of the organic silicon high temperature binder is less than 14, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0069] At 14-18, the coating has a high reflectivity to infrared radiation (1.4-15μm band), higher than 85%, and when the weight amount of the silicone high temperature adhesive is 16 parts, the reflectivity is 87%, the highest. The adhesion grade is 0, the coating edge is intact, without any peeling;
[0070] When it is higher than 18, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply, below 85%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0071] Taking into account the infrared (1.4-15 μm band and 4-5 μm band) reflection efficiency and adhesion of the coating, the weight amount of the silicone high temperature adhesive is preferably 14-18 parts, and the optimal value is 16 parts.
[0072] Example 6
[0073] On the basis of Example 1, only the amount of polyacrylate ammonium salt dispersant was changed, and the performance test was performed again, as shown in the following Table 4:
[0074] Table 4
[0075]
[0076] Note: The cross-cut test adopts the international standard ISO2409 "Coatings and varnishes - Cross-cut test" for grade assessment.
[0077] Conclusion: The above table shows that when the weight dosage of polyacrylate ammonium salt dispersant is less than 5 parts, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The dispersion of nanoparticles is less than 95%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0078] At 5-7, the coating has a high reflectivity to infrared radiation (1.4-15μm band), higher than 85%, and when the weight amount of polyacrylate ammonium salt dispersant is 16 parts, the reflectivity is 87%, the highest. The dispersion of nanoparticles is higher than 95%, and when the weight amount of polyacrylate ammonium salt dispersant is 16 parts, the dispersion of nanoparticles is 97%, the highest. The adhesion grade is 0, the coating edge is intact, without any peeling;
[0079] When it is higher than 7, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply, below 85%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0080] Taking into account the infrared (1.4-15 μm band and 4-5 μm band) reflection efficiency of the coating, the dispersion of nanoparticles and the adhesion, the weight amount of the polyacrylate ammonium salt dispersant is preferably 5-7 parts, and the optimal value is 6 parts.
[0081] Example 7
[0082] On the basis of Example 1, only the amount of anhydrous ethanol was changed, and the performance test was performed again, as shown in the following Table 5:
[0083] Table 5
[0084]
[0085]
[0086] Note: The cross-cut test adopts the international standard ISO2409 "Coatings and varnishes - Cross-cut test" for grade assessment.
[0087] Conclusion: The above table shows that when the weight amount of anhydrous ethanol is less than 17 parts, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0088] At 17-27, the coating has a high reflectivity to infrared radiation (1.4-15μm band), higher than 85%, and when the weight amount of anhydrous ethanol is 16 parts, the reflectivity is 87%, the highest. The adhesion grade is 0, the coating edge is intact, without any peeling;
[0089] When it is higher than 27, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0090] Taking into account the infrared (1.4-15 μm band and 4-5 μm band) reflection efficiency and adhesion of the coating, the weight amount of anhydrous ethanol is preferably 17-27 parts, and the optimal value is 21 parts.
[0091] Example 8
[0092] On the basis of Example 1, only the molecular weight of the polyacrylate ammonium salt dispersant was changed, and the performance test was performed again, as shown in the following Table 6:
[0093] Table 6
[0094]
[0095] Note: The cross-cut test adopts the international standard ISO2409 "Coatings and varnishes - Cross-cut test" for grade assessment.
[0096] Conclusion: The above table shows that when the molecular weight of the polyacrylate ammonium salt dispersant is lower than 100000 g / mol, the reflectivity of the coating to infrared radiation (1.4-15 μm band) drops sharply to less than 85%. The dispersion of nanoparticles is less than 95%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0097] At 200000-400000 g / mol, the reflectivity of the coating to infrared radiation (1.4-15 μm band) is high, higher than 85%, and when the molecular weight of the polyacrylate ammonium salt dispersant is 300000 g / mol, the reflectivity is 88%, the highest. The dispersion of nanoparticles is higher than 95%, and when the molecular weight of the polyacrylate ammonium salt dispersant is 300000 g / mol, the dispersion of nanoparticles is 97%, the highest. The adhesion grade is 0, the coating edge is intact, and there is no peeling;
[0098] When it is higher than 400000, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0099] Taking into account the infrared (1.4-15 μm band and 4-5 μm band) reflection efficiency of the coating, the dispersion of nanoparticles and the adhesion, the molecular weight of the polyacrylate ammonium salt dispersant is preferably 200,000-400,000 g / mol, and the optimal value is about 300,000 g / mol.
[0100] Example 9
[0101] On the basis of Example 1, only the coating thickness was changed, and the performance test was performed again, as shown in Table 7 below:
[0102] Table 7
[0103]
[0104]
[0105] Note: The cross-cut test adopts the international standard ISO2409 "Coatings and varnishes - Cross-cut test" for grade assessment.
[0106] Conclusion: The above table shows that when the thickness of the nano coating is less than 150μm, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The surface roughness Ra>0.1μm after 100 times of 300℃ high temperature cycle impact. The adhesion level is level 1, the edge of the coating is slightly peeled off, and the affected area is ≤5%;
[0107] At 150-180μm, the coating has a high reflectivity to infrared radiation (1.4-15μm band), higher than 85%, and when the nano coating thickness is 170μm, the reflectivity is 89%, the highest. The surface roughness after 100 times of 300℃ high temperature cycle impact is Ra=0.08μm=<0.1μm, indicating super smoothness. The adhesion grade is 0, the coating edge is intact, without any peeling;
[0108] When the thickness is higher than 180μm, the reflectivity of the coating to infrared radiation (1.4-15μm band) drops sharply to less than 85%. The surface roughness Ra>0.1μm after 100 times of 300℃ high temperature cycle impact. The adhesion level is level 1, the edge of the coating peels off slightly, and the affected area is ≤5%;
[0109] Taking into account the infrared reflection efficiency of the coating (1.4-15μm band and 4-5μm band), surface roughness and adhesion, the thickness of the nano coating is preferably 150-180μm, and the optimal value is 170μm.
[0110] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. An infrared heat radiation nano reflector for a road surface in-situ heat regeneration heating unit, characterized in that: The invention comprises a substrate, the surface of which is sprayed with a nano coating; the components of the nano coating comprise the following raw materials in parts by weight: 34 parts of nano titanium dioxide, 20-24 parts of nano aluminum oxide, 14-18 parts of an organic silicon high temperature binder, 5-7 parts of a dispersant, and 17-27 parts of anhydrous ethanol solvent; the average particle size of the nano titanium dioxide is 30-40 nm, and the average particle size of the nano aluminum oxide is 40-50 nm; the dispersant is a high molecular weight polyacrylate ammonium salt dispersant, and the molecular weight ranges from 100000 to 400000 g / mol.
2. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 1, characterized in that: The substrate is aluminum alloy 6061 or titanium alloy TC4.
3. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 1, characterized in that: The organosilicon high temperature adhesive is a MS polymer adhesive, specifically, GENIOSIL® XT55, which has an adhesive strength retention rate of not less than 80% in a high temperature environment above 320°C.
4. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 1, characterized in that: When preparing the nano coating, under a constant temperature and humidity environment, each raw material is accurately weighed, and nano titanium dioxide, nano aluminum oxide, silicone high-temperature binder, and dispersant are added to anhydrous ethanol in proportion to obtain a solution; then the solution is placed in a high-speed stirrer and stirred continuously at a speed of 1200-1400 rpm for 70-90 minutes until the solution has uniform color, good fluidity, and no visible agglomerates, thereby obtaining a nano coating.
5. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 1, characterized in that: The spraying preparation of the thermal radiation nano reflector includes two parts: substrate pretreatment and nano coating spraying and curing.
6. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 5, characterized in that: The substrate pretreatment comprises the following steps: Grinding: Use an automatic sandblasting machine for surface treatment or use 300-grit sandpaper for manual grinding until the surface roughness Ra is 0.9-1.1μm; Degreasing: Soak in acetone for 10-15 minutes for deep degreasing to completely remove oil and impurities; Rinse and dry: Rinse with deionized water at high pressure for 3-5 minutes to ensure no impurities remain, then dry.
7. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 5, characterized in that: When spraying and curing the nano coating, a spray gun is used to evenly spray the nano coating. The spray gun air pressure is stabilized at 0.45-0.55MPa, and the spray thickness is precisely controlled at 60-80μm. After the spraying operation is completed, it is cured for 70-90 minutes in a constant temperature and humidity environment.
8. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 7, characterized in that: Repeat spraying and curing 2-3 times, and the final coating thickness is 150-180μm.
9. The infrared heat radiation nano reflector for the road surface in-situ heat regeneration heating unit according to claim 4 or 7, characterized in that: The constant temperature and humidity environment is 25±2°C and 50±5%.
Citation Information
Patent Citations
Intelligent integrated optical component based on digital power control
CN105387393A
Infrared radiation roof based on phase change material
CN222101300U